Development of Interest in Healthy Lifestyle Among Students - Tiosova T. N. (Interactive science, 2020)
this article analyzes the results of a survey conducted among students of the faculty of Economics of the Vladivostok branch of the Russian Customs Academy. The main topic of the survey is the interest of students in the formation of a healthy lifestyle. During this research the method of the analysis of results of questioning among students and the analysis of the scientific literature reviewing this question was used.
Keywords: здоровый образ жизни; физическая культура; студенты; анкетирование; students; healthy lifestyle; questioning; Physical culture; второй курс; second year